Penguatan Strategi Pemasaran Digital Produk Home Decoration Pada UMKM Corrie Galery Kelurahan Sawojajar Kecamatan Kedungkandang Kota Malang - Yuliana, Rachma; Rokhmawati, Dian; Yuniarto, Eko (STIE Malangkucecwara, 2024)
Corrie Gallery makes various products made from fabric and thread as well as soap-based products, such as wall decorations that have value or are called